Donors and recipients: charities, NGOs and aid - Dang, Canh Thien (2019)
Non-profit organisations (NPOs) play an integral part in delivering public services and channelling development aid around the world. This thesis contains three papers on behaviour, motivations, and the accountability of these organisations.